Application of PBL Model to Improve Mathematics Learning Outcomes of Grade II Elementary School Students - Arrizqi Wahyu Putranto; Mushodikul Umam; Agung Deddiliawan Ismail (Politeknik Siber Cerdika Internasional, 2023)
This study aims to improve the learning outcomes and activeness of class II students in learning math material about time by applying the Problem-Based Learning model. This study used classroom action research, each cycle comprising two meetings. The subjects of this study were 29 students of grade II SD Muhammadiyah 9 Malang City. Data collection using observation instruments, interviews and documentation. The results show that applying the Problem-Based Learning model, cycle I get 87%, and cycle II gets 93%. Student learning outcomes in cycle I get an average of 89%, and cycle II get an average of 91%